Design, Properties, and TFT Application of Solution‐Processed In‐Ga‐Cd‐O Thin Films. Issue 5 (8th March 2018) - Song, Anran; Javaid, Kashif; Liang, Yu; Wu, Weihua; Yu, Jingjing; Liang, Lingyan; Zhang, Hongliang; Lan, Linfeng; Chang, Ting‐Chang; Cao, Hongtao
Abstract : Concerning the revolutionary future of electronic devices, high‐performance solution‐processable semiconductors have earned increasing academic and industrial research interests. In this paper, we synthesize In‐Ga‐Cd‐O semiconductor thin films via a solution method. Transparent amorphous/nanocrystalline oxide thin films with small surface roughness have been grown by controlling the relative ratio of Cd‐content. The present thin‐film transistor with an optimized Cd‐ratio exhibits a saturation field‐effect mobility up to 10 cm 2 V −1 s −1, an on/off current ratio of ≈1.3 × 10 9, and a threshold voltage shift of ≈2.6 V under −5 V gate bias of 10 000 s, which are superior or comparable to those reported values of solution‐processed conventional In‐Ga‐Zn‐O counterparts. Our results indicate that the proposed In‐Ga‐Cd‐O semiconductor would endow a promising transparent amorphous/nanocrystalline active material for electronic devices. Abstract : InGaCd x O thin films with various Cd‐ratios are synthesized via a facile solution method. With proper Cd‐ratios, the films possess transparent amorphous/nanocrystalline features with small roughness. The optimized thin‐film transistors exhibit superior electrical performance and bias stress stability compared with the conventional In‐Ga‐Zn‐O counterparts. The proposed InGaCd x O semiconductor would endow a promising transparent amorphous/nanocrystalline active material for electronic devices.